Differential adaptations of japonica rice to submergence stress during the tillering stage under various seedling cultivation and transplanting methods - Duan, Sumei; Zhang, Qianxi; Ai, Hao; Feng, Tingting; Zhou, Aifeng; Liu, Yi; Wang, Yuqin; Fang, Fei (Frontiers in Plant Science, 2025)
The response mechanisms of rice to submergence stress during the tillering stage remain unclear, and different seedling cultivation and transplanting methods may influence submergence tolerance. This study aimed to investigate the differential responses of rice to submergence stress under diverse combinations of seedling cultivation and transplanting methods, providing a theoretical basis for evaluating rice submergence tolerance. The japonica rice cultivar 'Nanjing 46' was used as the test material. Five combinations of seedling cultivation and transplanting methods (Y1–Y5, including direct seeding and hard-ground dry nursery substrate micro-sprinkler tray seedling combined with machine transplanting) were established, combined with four submergence durations (0 days/B0, 4 days/B1, 7 days/B2, and 10 days/B3), resulting in 20 treatments. Agronomic traits (plant height, tiller survival rate), physiological indices [peroxidase (POD) and superoxide dismutase (SOD) activities, malondialdehyde (MDA) and proline (PRO) contents, soil and plant analyzer development (SPAD) value], and yield data were analyzed to evaluate submergence tolerance. Growth Inhibition: Submergence retarded rice growth, causing leaf yellowing, senescence, and overall plant weakness, with more pronounced effects as submergence duration increased. Significant differences in plant height were observed among seedling cultivation methods and submergence durations. Over two-thirds of tillers survived under complete submergence for up to 7 days during the tillering stage. Submergence significantly affected POD and SOD activities, MDA and PRO contents, and SPAD values, characterized by initial increases followed by decreases in antioxidant enzyme activities, MDA accumulation, and PRO content elevation. Submergence Tolerance Variation: Seedling cultivation methods significantly influenced yield and submergence tolerance. Among treatments, direct seeding showed the poorest submergence tolerance, while hard-ground dry nursery substrate micro-sprinkler tray seedlings combined with machine transplanting performed best. This study demonstrated that rice can retain original plants and maintain a certain yield level under submergence for up to 7 days without special measures, and satisfactory yields can be achieved with appropriate remedial techniques and enhanced management. Seedling cultivation and transplanting methods affect submergence tolerance by regulating plant morphology and physiological adaptability, providing practical insights for optimizing stress-resistant rice cultivation patterns.